The right to freedom of enterprise: reflection from the banking sector in Vietnam - Pham, Thi Hong Nghia (Đại học Quốc gia Hà Nội, 2020)
The right to freedom of enterprise is recognized in Article 33 of Vietnam Constitution 2013, according to which all entities, including individuals and organizations, have the right to do business in the sectors and trades that are not prohibited by law. The right to freedom of enterprise inherited from the Constitutions of 1946, 1959, 1980 and 1992 and continuing to be recognized in the 2013 Constitution shows the constant attention that Vietnam has paid attention to the economic development of different entities in the society. However, the banking sector always carries high systematic risks; only one credit institution at risk may lead to the collapse of the whole system of credit institutions, the banking sector, and even a national economy or the world economy. As a result, in addition to recognizing the right to freedom of enterprise of business entities in the banking sector, the state also needs regulations to limit the rights to ensure the stability and development of the money market, the banking system, the economy of the sector considered as “lifeblood” of the national economy. This paper aims to illuminate on the debate about the protection of the right to freedom of enterprise in the banking sector by exploring two sets of issues. The first is how to recognize the right to freedom of enterprise in the banking sector under Vietnam law. The second area for investigation is the nature of constitutional protection, the meaning of the limit in the right to enterprise, freedom in the banking sector, and how the protection is typically provided for this right. The paper will tackle these issues based primarily on the analysis of the provisions of the 2013 Constitution and the 2010 Law on Credit Institutions. It is concluded that the right to the freedom of enterprise in the banking sector is a basic right, but shall be limited to ensure a stable and sustainable development of the banking sector.